2005
DOI: 10.1590/s0102-311x2005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of the human papillomavirus: a systematic quantitative review

Abstract: In order to better understand the exact mode and risk of vertical transmission in asymptomatic pregnant women, as well as the relationship between HPV transmission and mode of delivery, we have proposed this systematic quantitative review of prospective cohort studies. A comprehensive search was performed in the Cochrane Library, MEDLINE, LILACS, CANCERLIT, and EMBASE, as well as in the reference lists from the identified studies. Nine primary studies, which included 2,111 pregnant women and 2,113 newborns, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
19

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 26 publications
4
67
1
19
Order By: Relevance
“…HPV is one of the most prevalent sexually transmitted infections. Around 630 million people worldwide are infected with HPV; moreover, even 75-80% of sexually active people become infected with HPV at some point in their lives (7). Even though the prevalence of different HPV types varies across different geographic regions, types 16 and 18 are most frequently detected.…”
Section: Introductionmentioning
confidence: 99%
“…HPV is one of the most prevalent sexually transmitted infections. Around 630 million people worldwide are infected with HPV; moreover, even 75-80% of sexually active people become infected with HPV at some point in their lives (7). Even though the prevalence of different HPV types varies across different geographic regions, types 16 and 18 are most frequently detected.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a significantly higher rate of HPV 16/18 infection was found at birth when infants were delivered vaginally than when infants were delivered by cesarean (51.4% versus 27.3%) (Tseng et al, 1998). A systematic review (Medeiros et al, 2005) reported a higher risk of HPV infection after vaginal delivery than after cesarean section (RR: 1.8; 95%CI: 1.3-2.4). The risk of transmission has also www.intechopen.com been identified as increasing with the rupture of membranes; the longer time rupture of membranes occurred before delivery, higher risk of transmission (Tenti et al, 1999 Only a few studies have analysed the probability of persistence among babies born to HPVinfected mothers such as Rombaldi et al (2009) and Watts et al (1998) who have reported a very low proportion of persistent infection in infants (reported 0% in a 1 and 3-year followup study, respectively) whereas some reported very high proportions ranging from 27 to 56% (Fredericks et al, 1993;Kaye et al, 1994;Pakarian et al, 1994;Cason et al, 1995Cason et al, , 2005Syrjänen et al, 2000).…”
Section: Epidemiology Of Hpv Infection In Infant and Childrenmentioning
confidence: 99%
“…They showed that pooled mother-to-child HPV transmission was 6.5% and was higher after vaginal delivery than after cesarean section. The authors also showed that the combined relative risk of mother-to-child HPV transmission was 7.3 (Medeiros et al, 2005). Rombaldi et al determined the rate of maternal HPV transmission using PCR and nested multiple PCR on maternal cervical swabs and neonatal nasopharyngeal specimens.…”
Section: Nonsexual Mode Of Transmissionmentioning
confidence: 99%